SINERGISME TRADISI LISAN PARIKAN DAN INDUSTRI KREATIF FASHION DI YOGYAKARTA - Isna Maylani (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2022)
A parikan oral tradition is a form of oral tradition inherent in Javanese society, especially Yogyakarta. As part of a culture, parikan has its potential if it is used as a fashion commodity. This research talks about the synergism of the oral tradition and the creative industry elevated the parikan in fashion. The method used is a qualitative research method with a descriptive presentation, with oral data as primary data. Furthermore, it could be concluded that the use of parikan in fashion in Yogyakarta is a distinctive attraction for cultural activists and tourists. The promotion of values ​​of parikan in fashion goods is also an effective means of channeling noble values ​​and preserving culture. Keywords: Creative Industry, Oral Tradition, Parikan